A remote controllable fiber-type near-infrared light-responsive actuator. Issue 81 (8th June 2017) - Shi, Qiuwei; Li, Jiahui; Hou, Chengyi; Shao, Yuanlong; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi
Abstract : A fiber-type near-infrared light-responsive actuator exhibited significant features: remote control, low temperature permitted actuation and effective driving of the shape change of a fabric. Abstract : A novel near-infrared (NIR) light-responsive sodium polyacrylate (PAAS)/graphene oxide (GO) fiber with a torsional pre-deformation structure is reported to realize remote control actuation. The torsional pre-deformed PAAS/GO fiber exhibited various actuation phenomena, under the control of a low powered near-infrared light (50 mW cm −2 ), such as rotating in a low-temperature range (<25 °C), rolling a distance of 10 times of its diameter within 10 s, and even driving the shape change of a fabric (the weight is as high as 20 times of the fiber itself).